CONTROLLING ENVIRONMENTAL DAMAGE DUE TO DEVELOPMENT IN THE PERSPECTIVE OF CONSTITUTIONALISM IN THE INDONESIAN LEGAL SYSTEM - Junita, Putri; Hilal, Cut Anastasia Nurul; Wibowo, Fiana Suryaningtyas; Azzahra, Hajar Auliya (Universitas Islam kadiri, 2024)
Controlling environmental damage due to development is an important issue in the context of the constitutionalism of the Indonesian legal system. With the rapid development, the principles of environmental sustainability are often ignored, resulting in ecosystem degradation and a decrease in the quality of life. From a constitutional point of view, the 1945 Constitution of the Republic of Indonesia places environmental protection as part of human rights and state responsibility. This article examines various legal and policy instruments used in the Indonesian legal system to control environmental damage, including the role of the Constitutional Court in enforcing environmental protection. Furthermore, this analysis highlights the challenges in implementing environmental policies and provides recommendations for strengthening legal enforcement mechanisms to achieve sustainable development. The research method we will use is a normative legal method which we take from literature data and then summarize. In this discussion we has contained information about what kind of development in Indonesia is based on constitutional provisions.